POWER RELATIONS PRACTICES IN HIGHER EDUCATION ELECTRONIC LIBRARY IN BALI - I Putu Suhartika; I Wayan Ardika; I Ketut Ardhana; I Nengah Punia (E-Journal of Cultural Studies, 2022)
Electronic library is apart of the implementation of information and communication technology in libraries as mandated in Law No. 43 of 2007 and SNP 010: 2011. There are various obstacles in developing electronic library which are especially related to the power relations of actors. Therefore, this study aims to analyze the practice of power relations in the electronic libraries of universities in Bali so that the processes, forms, and implications of these power relations can be revealed. This study uses 17 (seventeen) library actors consisting of the Head of the Library, Vice Chancellor I, Librarians, Programmers, and Users spread over 5 (five) universities in Bali as informants who were interviewed semi-structured. This study uses Foucault's theory of power relations as a grand theory, and is supported by Derrida's theory of deconstruction and Gramsci's hegemony. The results showed that the practice of power relations in university libraries in Bali is mainly based on the actor's knowledge. This is in accordance with Foucault's perspective where knowledge can produce power in the electronic library. However, the practice is also based on the structural position of actors, so that power relations are not always balanced, but also in the form of domination, negotiation, and hegemony which are depicted in power frames. The practice has good implications for libraries, especially for users, librarians, programmers, and library collections, although in certain cases, power relations provide gaps between these actors. Keywords: electronic library, power relation, domination, deconstruction, and hegemony